Pola-pola Morfofonemik Arab dalam Alquran - Taftazani, Sofjan (Research and Development Institution, Darussalam Institute for Islamic Studies, 2016)
The article is as a library study being made to describe the patterns of morphophonemics (variation in the form of Morphemes because of Phonetic factors) of the Arabic language in Qur’an. This study concerns three patterns of morphophonemics such as; (1) hadzf, (2) ziyâdah and (3) ibdâl. Hadzf concerns phonem ya, alîf, wau, ta mudhara’ah, ta istif’ala, and ha mashdar, ziyâdah consists of alîf, ya, wau, ta and ha saktah; and ibdâl consists of (a) ibdâl without idgham that relates to ibdâl ta-dal and tha, dzal-dal, wau and hamzah-ta, alîf-wau, sin-shad, ya-alîf, ta marbuthah-ta majrurah and (b) ibdâl with idgham that relates to ibdâl ta-tsa, dal, zay, sin, shad and dhad. This three morphophonemic patterns relate to rasam, qirât, imla and syaraf.